Community Voices: Perspectives on Renewable Energy in Nunavut - McDonald, Nicole C.; Pearce, Joshua M. (ARCTIC, 2012)
Nunavut communities currently depend on imported diesel fuel for virtually all of their energy needs. This dependency not only hinders the ability of communities to be self-sufficient, but also has negative impacts on their environment, health, and social well-being. The current practices waste 65% of the energy created and place a serious economic strain on the society by consuming 20% of the government’s annual budget. Although renewable energy technologies (RETs) could partially offset diesel use, there is a lack of sufficient information to mold appropriate policy. This investigation of community perspectives contributes to information needed to develop sustainable energy policies for Nunavut. Open-ended interviews with approximately 10 members from each of three communities were studied using logical analysis, pattern coding, and content analysis. The respondents’ greatest concerns about energy in Nunavut are the impacts of technology on the environment and the economy and the lack of government initiatives to explore RETs. In identifying these concerns, respondents expressed an overwhelming need to protect their land and wildlife, likely stemming from Nunavut’s dominant Inuit culture. Moreover, Nunavummiut generally supported wind and solar power in their community, but greatly opposed hydropower, though some of these views on hydropower might shift if better information were available to residents. Finally, respondents suggested a variety of community-accepted actions that could be used to increase RET expansion in Nunavut. These actions fit into four categories: policy development, economics, suitable RETs, and capacity and knowledge building.